Numerical Analysis of Time-Dependent Strength and Stiffness in Palm Oil Fuel Ash-Stabilized Soil: Early and Long-Term Effects - Al-Dalain, Nour A. W.; Ezreig, Ali M. A.; Ismail, Mohd A. M. (Civil Engineering Journal, 2024)
Over the years, investigating the behavior of soft soil, stabilized using different techniques, has been recognized as a critical priority for geotechnical engineers. Numerous soil constitutive models have been utilized to simulate stabilized soil behavior, improve strength and ductility, and analyze load-deformation responses. However, further investigation is required to study stabilized soil's time-dependent strength and stiffness, especially at an early curing age. Early strength and stiffness development is crucial in engineering construction for improving building quality and efficiency and minimizing crack risk. Furthermore, estimating UCS from an early age aid in safety evaluation and ground-improvement analysis. Researchers are increasingly recognizing palm oil fuel ash (POFA) as an eco-friendly alternative to traditional soil stabilizers due to its abundant availability. This study proposes an advanced concrete constitutive model to simulate the time-dependent strength and stiffness of POFA-stabilized and cement-stabilized soil due to pozzolanic interactions. The model accurately measures strength and stiffness improvement from an early curing age to 28 days using finite element analysis (FEA) before then comparing the experimental results. Based on the experimental results, the UCS values of palm oil fuel ash-stabilized soil grew to 3.18 MPa and 3.89 MPa after seven and 28 days with an optimum content of 30% (POFA): 10% Magnesium Oxide (MgO). It exhibited a significant increase in early strength with 64.02% compared with cement-stabilized soil. For stiffness results, a slight increment of 9.26% was observed. Employing FEM, the sensitivity of the parameters to stress-strain behavior was investigated. Finally, the validity of the concrete constitutive model to predict the time-dependent strength and stiffness of stabilized soil was proved. Doi: 10.28991/CEJ-SP2024-010-05 Full Text: PDF